Методика аппроксимации кривых намагничивания вентильных индукторно-реактивных двигателей - Зинченко, Елена Евгеньевна; Финкельштейн, Владимир Борисович (НТУ "ХПИ", 2009)
На базе функций сплайн-интерполяции и сплайн-аппроксимации системы MathCAD 2001 предложена методика аппроксимации кривых намагничивания вентильных индукторно-реактивных двигателей и получения зависимости потокосцепления от тока и угла поворота ротора, которая необходима для математического описания процессов в них и расчета их параметров и характеристик.

The paper presents a technique of magnetization curves approximation for switched reluctance motors and determination of magnetic linkage versus current and rotation angle of the rotor on the basis of MathCAD-2001 spline approximation and spline interpolation. The dependence is used for mathematical formulation of processes in switched reluctance motors and calculation of their parameters and characteristics.
A technique of magnetization curve approximation for switched reluctance motors
Keywords: определение линейного участка; зависимость потокосцепления; кривые намагничивания; MathCAD 2001; switched reluctance motor; magnetization curves approximation; MathCAD-2001 based technique